Oeis Complex: a rare Case Report - Sowmya M; Shwetha Shashidhar (International Journal of Medical Research and Review, 2014)
We describe a case of OEIS complex [Omphalocele-Exstrophy of the Bladder-anal imperforation-spina bifida] a rare congenital malformation complex. It results from improper closure of ventral abdominal wall due to failure of convergence of cephalo-caudal and lateral foldings of embryo during development, with asociated defects in development of cloaca and urorectal septum. A second gravida, with previous normal obstetric history of 35 wks of gestation spontaneously delivered a live pre term baby with gross malformations of a large omphalocele containing kidney,liver and intestines, bladder exstrophy, anal imperforation and spina bifida. Patients with OEIS complex require the care of a multidisciplinary team with multiple surgeries with its own potential complications. Hence, early antenatal diagnosis and evaluation provides prognostic information, treatment options, decisions concerning the management and the plan for specific needs at birth.